ADVANTAGES OF BAMBOO AS A BIOMATERIAL FOR SUSTAINABLE BUILDING CONSTRUCTION (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Architects as designers, are well aware that material selection for sustainable building construction has become a major problem. Each construction material must have the design value required for structural analysis. The sustainability of bamboo to supply building construction materials can be guaranteed as long as its management is carried out properly. Bamboo as a monocot plant can grow very fast, with the rate of photosynthesis demonstrating excellent sinusoidal equations to form its superiority. Therefore, bamboo as a wood substituting material for construction is very promising. However, bamboo is an inhomogeneous natural material with very high variations, including the value of the allowable stress and its reference strength. With certain preservation, bamboo can last more than 20 years. This study aims to determine the optimal preservation technique based on a number of research results before the material becomes an option for sustainable building construction. The method used is descriptive qualitative. The results are based on a number of studies that have shown that the advantages of bamboo are based on its strength, which is largely contributed by sclerenchyma cells which are bound in its vascular bonds to form bamboo strength and stiffness. To maintain and increase its strength, preservation is needed. One way to increase the superior quality of bamboo is to use a combination of biological preservation methods (determining the period of cutting / harvesting bamboo in the dry season, especially in March, April and May as the best cutting times in Indonesia, which is an area with a wet tropical climate) and chemical (vertical soak diffusion system using camphor with kerosene and / or smoking with sulfur), is a way of preservation that can increase its superior value as a construction material. Keywords: bamboo, building, construction, material, sustainable.